Current status of ATP-ase proton pump inhibitor complexation with cyclodextrins - L. Marzocchi; J. R. Moyano; A. Rossi; P. Muñoz; M. J. Arias; F. Giordano (ՀՀ ԳԱԱ հրատ.)
The inclusion complexes of cyclodextrins with drugs where the changes brought to the physical, chemical and biological properties of the guest molecules endow the final product with considerable pharmaceutical potential.
Keywords: Biology; Biochemistry; Pharmacology